The Comparative Analysis of Inpatient Service at Public Hospitals and Private Hospitals in Order to Improve Patient Satisfication : A Literature Review - Nadya Salsabila; Khoirunnisa Ghefira Yusrani; Safinah Annajah; Kazhima Alma Azzahra; Rossa Shafira Nur Sabrina (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Indicators of patient satisfaction in providing quality health services are measured based on the main dimensions of quality, namely reliability, responsiveness, assurance, empathy, and tangible. The five aspects of the quality dimension have not been applied to hospital inpatients, this is shown from data from the Indonesian Ministry of Health in 2018 that 60% of hospitals in Indonesia have not met the needs of efficient services and have not implemented acceptable and affordable service standards. The research method used in this research is a literature review study, by collecting several articles using online search sources through Google Scholar and journal databases, such as PubMed, Elsevier, and DOAJ. The results of the literature review of 8 articles show that private hospitals almost entirely perform better than public hospitals in all five dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. However, the assessment also depends on the public and private hospitals where the researcher conducted the study. These dimensions of service quality are considered very important for healthcare facilities to improve patient satisfaction and provide optimal care in both public and private hospitals.